Forensic entomology workshop 2023 - Idorus, Mohd Yusri (Faculty of Medicine, 2023)
Faculty of Medicine and IMMB are honored to host and welcome lecturers and students from the National University of Singapore (NUS) who participated in the Forensic Entomology Workshop 2023, starting from February 20 until February 24, 2023. This five-day workshop consisted of a series of lectures, discussions, and fieldwork attended by 38 NUS students, including 17 Master's students in forensic science. The delegation from NUS was led by Assoc. Prof. Stella Tan (Associate Provost for Student Conduct and Director of the Forensic Science Program at NUS), Dr. Shawn Lee, and Mr. Ng Wei Bo.